The Importance of Organic Agriculture and Şanlıurfa Farmers’ Perspectives on Organic Products - Ayşe Çalık (Turkish Journal of Agriculture: Food Science and Technology)
Sustainable agriculture can be defined as the creation of an agricultural structure using agricultural technologies that do not harm the environment in addition to the protection of Natural Resources in the long term. In Turkey, as in the developed countries of the world, intensive (traditional or intensive) agricultural production is used without considering the negative consequences of processing techniques and technologies while using synthetic production inputs without supervision. Today, these applications have started to attract as much attention as waste industry or urban pollution with their effects on the determination of natural balance and the ability to create life hazard that can reach all living beings as well as human beings through the food chain. Therefore, organic farming techniques that meet quality, health and environmental standards play a key role by avoiding the use of unnatural inputs such as pharmaceuticals, synthetic fertilizers. Organic agriculture, which is important for the reflection of sustainable agriculture in practice, has started to be seen as a necessity, especially with the development of environmental awareness in recent years. In this study, it is aimed to explain the basic principles of organic agriculture, which we believe are necessary for sustainable agriculture in the 8 villages, namely Umut, Günbalı, Yenisu, Mehmetçik, Güçlü, Akpınar, Güzel, Anaz and 3 towns (Kısas, Konuklu and Çamlıdere) in Şanlıurfa. According to the results of the survey, almost 30% of farmers were found to grow organic products. At the time of purchase, they answered the question of which products do you pay attention to organic, and more than half (54.8%) of the surveyed farmers responded that they pay attention to food. 45.18% of the surveyed farmers stated that they did not pay attention to anything in shopping.